The contribution of connectivism in learning by competencies to improve meaningful learning - Baque, Patricia Gabriela Chong; Cevallos, María Andrea Mendoza; Natasha, Zambrano Barreiro Mariana; Lino, María Magdalena Barahona (International research journal of management, IT and social sciences, 2020)
Currently, technology influences the evolution of cultural, social, and educational changes is no exception, there is an evolution in the ways of learning and teaching, which has become a challenge, especially in social spheres where technology was unlikely to be used as an educational means since there was no access to it. That is why this article seeks to expose the role that connectivism has as a learning theory of the digital age and highlight its contribution in the formation of competences to achieve meaningful learning, based on the results obtained through a desk study. o Desk Research which allowed a critical and reflective review of previous research on the subject. Finding that technology plays a fundamental role in the integration of connectivism where students will discover knowledge using strategies and skills to act or apply solutions to simulated or real cases, discovering, transforming, creating, or applying competences.